Nonstandard l+l- processes in relativistic heavy-ion collisions - Almeida, L. D. [UNESP]; Natale, A. A. [UNESP]; Novaes, S. F. [UNESP]; Boli, O. J.P. (American Physical Society (APS), 1991)
We study lepton pair production in heavy-ion collisions with emphasis on nonstandard contributions to the QED subprocess l+l-. The existence of compositeness of fermions and/or bosons can be tested in this reaction up to the TeV mass scale. We show that for some processes the capabilities of relativistic heavy-ion colliders to disclose new physics surpass the possibilities of e+e- or pp machines. In particular, spin-zero composite particles which couple predominantly to two photons, predicted in composite models, can be studied in a broad range of masses. © 1991 The American Physical Society.